2020
DOI: 10.1016/j.anbehav.2019.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Scent-marking strategies of a solitary carnivore: boundary and road scent marking in the leopard

Abstract: The version presented here may differ from the published version or from the version of the record. Please see the repository URL above for details on accessing the published version and note that access may require a subscription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 41 publications
2
19
0
Order By: Relevance
“…At finer spatial scales, hyena latrine use was also consistent with our prediction of an economical marking strategy. Specifically, we found that latrines in this ecosystem were frequently located along human-made unsealed roads, which is consistent with other species in this environment (leopard, Panthera pardus, Rafiq et al 2020), and elsewhere (e.g. Iberian wolf, Barja et al 2004).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…At finer spatial scales, hyena latrine use was also consistent with our prediction of an economical marking strategy. Specifically, we found that latrines in this ecosystem were frequently located along human-made unsealed roads, which is consistent with other species in this environment (leopard, Panthera pardus, Rafiq et al 2020), and elsewhere (e.g. Iberian wolf, Barja et al 2004).…”
Section: Discussionsupporting
confidence: 87%
“…brown bear Ursus arctos horribilis rubbing trees, McTavish and Gibeau 2010). Thus, road creation may not only influence animal patterns and space use (reviewed by Trombulak and Frissell 2000), but may also impact animal communication systems (Krofel et al 2017;Rafiq et al 2020). In this context however, it worth considering the possible origin of road-related marking behavior in this and other species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cheetahs visited marking sites more frequently compared with leopards, but leopards may be more flexible in marking as they exhibit a boundary scent‐marking strategy (Bothma & Coertze, 2004; Rafiq et al, 2020). Cheetahs may also need to return quicker to marking sites as it is suggested that cheetah marking fluid loses its attraction to conspecifics after only 24 hours (Eaton, 1974).…”
Section: Discussionmentioning
confidence: 99%
“…For example, some habitat features operate as attractors and increase local space use, such as riparian vegetation for brown bears ( Ursus arctos ) ( 31 ). Scent-marking sites of carnivores, such as Eurasian lynx ( Lynx lynx ) ( 32 ), Sunda clouded leopard ( Neofelis diardi ) ( 33 ), leopard ( Panthera pardus ) ( 34 ), snow leopard ( Panthera uncia ) ( 35 ), gray wolf ( 36 , 37 ), spotted hyena ( 38 ), and European badger ( Meles meles ) ( 39 ), are often frequently visited, can include conspicuous locations such as latrines, and are distributed unevenly across the landscape, particularly when linked to key habitat features ( 32 ), and can include conspicuous locations such as latrines. Even more pronounced causes for concentrated space use, ubiquitous among carnivores, are dens and other breeding sites during the period when juveniles are immobile ( 38 , 40 43 ).…”
Section: Discussionmentioning
confidence: 99%